A potential link between aberrant expression of ECRG4 and atrial fibrillation - Zhang, Zuojing; Wang, Wei; Zhang, Yuxin; You, Xingji; Wu, Jingxiang (Frontiers in Oncology, 2023)
Abstract: Patients undergoing perioperative radical esophagectomy are at risk of experiencing cardiovascular complications. Research shows that the incidence of intraoperative and postoperative myocardial injury in patients with esophageal cancer can be as high as 31.4% and 14.3% of new-onset atrial fibrillation under the triggers of intraoperative stress, which is significantly higher than the average 8% incidence of myocardial injury in other non-cardiac surgery and 2.9% incidence of atrial fibrillation in thoracoscopic lung cancer surgery. In patients undergoing radical esophagectomy, the perioperative risk of myocardial injury and atrial fibrillation may be attributed to specific genes. Esophageal cancer-related gene-4 (ECRG4), a 148 amino acid propertied and new tumor suppressor, that is initially cloned from the normal esophageal epithelium, was found to be expressed not only in esophageal tissues but also in cardiomyocytes. In the heart, ECRG4 shows greater expression in the atria than in the ventricles, which accounts for its heterogeneity. Downregulation of ECRG4 expression level correlates with esophageal cancer, as well as myocardial injuries and arrhythmias. As a result, this review summarizes the susceptibility gene, ECRG4 and its associated molecular mechanisms in esophageal cancer patients with atrial fibrillation and myocardial injury. The review begins by describing ECRG4's biological background, examines its expression in the cardiovascular system, and discusses its potential role in atrial fibrillation. Afterward, it will be discussed as a possible early target of doxorubicin-induced cardiotoxicity, as well as how it can be used in the treatment of tumors and arrhythmias, and provides a novel strategy to reduce the occurrence of such perioperative cardiovascular adverse events in the context of esophageal cancer.